An Oak Spring Herbaria : herbs and herbals from the fourteenth to the nineteenth centuries : a selection of the rare books, manuscripts and works of art in the collection of Rachel Lambert Mellon /: herbs and herbals from the fourteenth to the nineteenth centuries : a selection of the rare books, manuscripts and works of art in the collection of Rachel Lambert Mellon. (2009) - Tongiorgi Tomasi, Lucia; Willis, Tony; Argetsinger, Mark
No abstract available